The Highest Retail Price (HET) of Subsidized Fertilizer at the Farmer’s Level in South Sumatra Rice Farming, Indonesia - Elisa Wildayana; M. Yamin Hasan; M. Edi Armanto; Imron Zahri; Dessy Adriani; Ranty Fitria Sari; Nursittah Nursittah; Fitri Lestari; Reszki Oktavia (Muhammadiyah University Press, 2018)
The research objective is to analyze the subsidized fertilizer price (HET) at the hand of farmers of rice farming in South Sumatra province. The sampling method was disproportionate stratified random sampling with four land typologies. The field data were collected through observation, interviews with respondents. The use amount of fertilizers on all typologies effected significantly different to rice yields. In the lebak ricefields, the influence of Urea, NPKPhonska and KCl together effected significantly different, but not significantly different for each use of fertilizers. The use cost of Urea affected rice yields and income of farmers significantly different for all ricefields. Eligible HET price received by farmers has to be lower than the real HET price. Determination eligible HET price has to consider soil productivity and accessibility (dam, water gates, water pump, road, infrastructure, local retail and others).